JENIS AVES DAN MAMALIA DIURNAL YANG MEMANFAATKAN JAMBU TANGKALAK (Bellucia pentamera) SEBAGAI SUMBER PAKAN DI KEBUN RAYA SAMBAS - Haryono, Aldi; Prayogo, Hari; Erianto, . (Universitas Tanjungpura, 2019)
Sambas Botanical Garden is an ex-situ conservation area, in its management there is the term Vak, which is a small management area with care and supervision that is more focused on the inside plants, Bellucia pentamera in the management of Vak is very limited and cut down, but actually Bellucia pentamera is forest plant which has the criteria of providing fruit almost all year long and is widely used by most wildlife. The study aims to record species of aves and diurnal mammals that use Bellucia pentamera as a source of feed for wild animals in the Sambas Botanical Gardens. The research was carried out in the management area and secondary forest, each represented by three growing places, namely hills, foothills and riparians. The study was conducted in July-August with a survey method by observing direct observation at the point of tangkalak guava stands with repetitions three times. The results showed that seven types of aves were found, namely Chloropsis sonnerati, Dicaeum trigonostigma, Dicaeum trochileum, Pycnonotus goiavie, Chloropsis cochinchinensis, Zosterops palpebrosus, and Arachnothera crassirostris, There are four types of mammals found, namely Macaca fascicularis, Sundasciurus lowii, Callosciurus prevostii, and Callosciurus orestes.Keywords: Aves, Bellucia pentamera, Feed, Mammals